Kriteria Alat Evaluasi Pembelajaran Bahasa - Siti Fatinah (Kantor Bahasa Provinsi Maluku Utara, 2013)
Every learning activity, including language learning, needs to be evaluated in order to measure the success rate of the learners. The learning success is measured by either test or non-test. Evaluation tool should have good validity and reliability. in other words, language test should meet the criteria of validity and credibility. In order to meet the criteria of validity, the language tests should be estimated by using validity estimation formulas, such as Pearson product-moment correlation coefficient or Spearman rank-correlation different.Moreover, in order to determine the reliability level of language test, there are six reliability estimation formula used. There are (1) re-test reliability, (2) the two-sided reliability, (3) Kuder-Richardson formula reliability 20, (4) Kuder-Richardson formula reliability 21, (5) Alpha Cronbach reliability, and (6) parallel formed reliability.